الضغوط النفسية لدى أساتذة الرابعة متوسط - عبد القوي, وسام; ميلودي, سليمة (University of Eloued جامعة الوادي, 2021)
الملخص: تسعى هذه الدراسة إلى التعرف على مدى شعور أساتذة التعليم المتوسط(السنة الرابعة متوسط) بالضغوط النفسية بسبب مختلف التغيرات التي مست المنظومة التربوية في ظل جائحة كورونا وتماشيا مع طبيعة الموضوع تم الاعتماد على المنهج الوصفي التحليلي,ولجمع البيانات من الميدان تم تطبيق الاستبيان كأداة, حيث طبقت على عينة من الأساتذة والأستاذات ببعض متوسطات بلدية الوادي وقدر عددهم 50أستاذا وأستاذة. أسفرت هذه الدراسة على نتائج هامة نذكر منها: • مستوى الضغوط النفسية لدى أساتذة تعليم السنة الرابعة متوسط متوسطة. • وجود فروق دالة إحصائية في الضغوط النفسية لدى أساتذة التعليم المتوسط تعزى لمتغير الجنس. • عدم وجود فروق دالة إحصائية في الضغوط النفسية لدى أساتذة التعليم المتوسط تعزى لمتغير الخبرة. • عدم وجود فروق دالة إحصائية في الضغوط النفسية لدى أساتذة التعليم المتوسط تعزى لمتغير الحالة العائلية. Abstract: This study seeks to identify the extent to which teachers of middle education (fourth year average) feel psychological pressure due to the various changes that affected the educational system in light of the Corona pandemic. It was applied to a sample of male and female professors in some averages of the municipality of the valley, and their number was estimated at 50 male and female teachers. This study resulted in important results, including: • The level of psychological stress among teachers of the fourth year, average, average. • There are statistically significant differences in psychological stress among middle school teachers due to the gender variable. • There are no statistically significant differences in psychological stress among middle school teachers due to the variable of experience. • There are no statistically significant differences in psychological stress among middle school teachers due to the variable of family status.
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: الضغط النفسي; Stresser; Stress